2012
DOI: 10.1021/jp207858x
|View full text |Cite
|
Sign up to set email alerts
|

Short-Range Order and Dynamics in Crystalline α-TeO2

Abstract: The short-range order and dynamics in crystalline α-TeO2 have been investigated by neutron and X-ray total scattering and by Rietveld refinement of neutron diffraction data. The true lengths of the two bonds in a Te–O–Te bridge are 1.882(1) and 2.117(1) Å, and the high valence, 1.293, of the strong, short bond is balanced by the low valence, 0.686, of the weak, long bond. The root-mean-square (rms) thermal variation, 0.083(1) Å, in the long bond length is nearly twice the rms thermal variation, 0.048(1) Å, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
(90 reference statements)
0
20
0
Order By: Relevance
“…The good agreement between the short Te-O bond lengths for Na10 and K10, and for Na19 and K20 reported in Table 2, is evidence that the contribution from in is very small and negligible: In a Te-O-Te bridge, there is a balance between the lengths and valences of the short and long bonds [15]. Thus, if the short bonds in glasses with different alkali are the same length, then the lengths of the long bonds may be expected to also be the same.…”
Section: The Isostoichiometric Difference Methodmentioning
confidence: 56%
See 2 more Smart Citations
“…The good agreement between the short Te-O bond lengths for Na10 and K10, and for Na19 and K20 reported in Table 2, is evidence that the contribution from in is very small and negligible: In a Te-O-Te bridge, there is a balance between the lengths and valences of the short and long bonds [15]. Thus, if the short bonds in glasses with different alkali are the same length, then the lengths of the long bonds may be expected to also be the same.…”
Section: The Isostoichiometric Difference Methodmentioning
confidence: 56%
“…a value taken from Barney et al [15] b value derived from the crystallographic thermal parameters reported by Tagg et al [20] c value estimated in this study; see …”
Section: Appendix 2: Broadening For T(r) Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetragonal α-TeO 2 polymorph was known much earlier than the others [17][18][19][20]. They can be described as different arrangements of corner or edge sharing TeO 4 unit (the distorted trigonal bipyramids) with two longer Te-O bonds (axial bonds) and two shorter ones (equatorial bonds) [21][22][23]. Amorphous TeO 2 has the networks that the basic structural unit is a TeO 4 polyhedron with a lone pair of electrons in one of its equatorial sites and varies with dopants [23,24].…”
Section: Theory and Calculationsmentioning
confidence: 99%
“…From the reference distances R (≈ 2.08, 1.89, 1.99 and 1.75 Å for crystalline and amorphous TeO 2 and GeO 2 , respectively [17,22,24,25,[52][53][54][55]) and the self-consistent field functions [56,57], the group overlap integrals S dpt , S dpe , S s and A are calculated and given in Table 1. According to the optical spectral analysis for Cu 2 + in the studied systems and some oxides [14,16], the cubic field parameters Dq and the orbital reduction factors N can be obtained as given in Table 1.…”
Section: Theory and Calculationsmentioning
confidence: 99%